Towards a shared vision and action frame for community forestry in Liberia: Proceedings of the First International Workshop on Community Forestry in Liberia, Monrovia, 12-15 December 2005 (Center for International Forestry Research, 2005)
This volume contains proceedings of a historic workshop held in December 2005 that has brought clarity to the concept of community forestry in Liberia. The workshop addressed a wide range of issues pertaining to community forestry, based on presentations from a range of experts, local community representatives, policy makers, researchers and the donor community. The ‘Monrovia Declaration’ adopted by the wide cross-section of stakeholders in Liberian forestry who attended the workshop, sets out a framework for future action on community forestry based on a common understanding of how the concept can be made practical in the Liberian context. It was the unanimous view of all workshop participants that community forestry had great potential to act as the motor for sustainable development of Liberia’s rural areas, and within an integrated framework that will help safeguard the country’s rich and diverse forest for posterity.